(untitled) (Conference Zone, 2022)
Islamic banking refers to bank operations that adhere to Sharia law. The Sharia law is in opposition to the fundamental principles of banking because it forbids the collection of interest as well as any transactions that allow for speculation. Meeting people’s financial requirements while adhering to Sharia law is thus a difficulty for Islamic banking. It appears that Islamic banks have discovered a business strategy that enables them to do so. We may learn more about the management system used by Islamic banks in this article.